A COMPARATIVE ASSESSMENT OF THE EFFECT OF MINERALOCORTICOID RECEPTOR ANTAGONISTS ON CHANGES IN GALECTIN-3 AND MMP-1 FIBROSIS MARKERS IN PATIENTS WITH CHRONIC CARDIAC FAILURE COMBINED WITH TYPE 2 DIABETES MELLITUS WITH MANIFESTATIONS OF MYOCARDIUM DYSSYNCHRONY - Rudenko, T. A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
A comparative assessment of the effect of mineralocorticoid receptor antagonists on changes in galectin 3 and matrix metalloproteinase 1 fibrosis markers has been carried out on 106 examinations (average age (69 + 10.37) years) with type 2 DM and CCF of ischemic nature of I-IV FC according to NYHA with retained systolic function of the left ventricle and manifestations of myocardium dyssynchrony. All the patients were divided into 3 groups depending on the intake of mineralocorticoid receptor antagonists. Myocardium dyssynchrony was assessed according to the generally accepted technique; the volume faction of interstitial collagen was measured using the formula of J. Shirani et al.; galectin-3 and matrix metalloproteinase-1 levels – using the immunoenzyme method according to the manufacturer’s manual. The data was processed using the methods of parametric and non-parametric statistics. It was discovered that the myocardium dyssynchrony development percentage in the group of patients not taking mineralocorticoid receptor antagonists was higher than in the group of patients taking spironolactone or eplerenone. An increase in fibrosis marker levels was shown in the spironolactone intake group compared with the group of patients taking eplerenone. Mineralocorticoid receptor antagonist intake requires blood potassium level control and case monitoring of manifestations of dyssynchrony and myocardial fibrosis.